2014
DOI: 10.1016/j.janxdis.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Attention Bias Modification Treatment for children with anxiety disorders who do not respond to cognitive behavioral therapy: a case series

Abstract: Evidence is emerging to support the promise of Attention Bias Modification Treatment (ABMT), a computer-based attention training program, in reducing anxiety in children. ABMT has not been tested as an adjuvant for children with anxiety disorders who do not respond to Cognitive-Behavioral Therapy (CBT). This case series presents findings from an open trial of ABMT among six children (four girls; M age =11.2 years) who completed a CBT protocol and continued to meet diagnostic criteria for an anxiety disorder. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 41 publications
2
26
1
Order By: Relevance
“…This limitation compromises confident conclusions concerning attentional change in two case study series. Bechor et al (2014) carried out one of these using only 6 clinically anxious children, aged 10 to 13 years. Children were given the avoid-threat ABM procedure used by Amir, Beard, Taylor, et al (2009), and across the 4-week period mean reduction on all the self-report measures of anxiety was significant.…”
Section: Impact Of Extended Abm On Anxiety When Its Impact On Attentimentioning
confidence: 99%
“…This limitation compromises confident conclusions concerning attentional change in two case study series. Bechor et al (2014) carried out one of these using only 6 clinically anxious children, aged 10 to 13 years. Children were given the avoid-threat ABM procedure used by Amir, Beard, Taylor, et al (2009), and across the 4-week period mean reduction on all the self-report measures of anxiety was significant.…”
Section: Impact Of Extended Abm On Anxiety When Its Impact On Attentimentioning
confidence: 99%
“…Other interventions instead have been configured to enhance attentional control (e.g., Roughan & Hadwin, 2011;Hadwin & Richards, 2016; see also Owens, Koster & Derakshan, 2013;Sari, Koster, Pourtois & Derakshan, 2015 for similar work with adult populations). Researchers have demonstrated that interventions designed to directly alter attentional functioning can serve as a positive adjunct to more traditional CBT interventions for anxiety reduction in individuals who experience elevated anxious affect and who demonstrate associated attentional difficulties (Schechner et al, 2014), and may be useful for children and young people who do not show positive outcomes following conventional CBT (e.g., Bechor et al, 2014).…”
Section: Translational Implicationsmentioning
confidence: 99%
“…First, it is brief, with the modal treatment course spanning four weeks with two 15-minute sessions per week. Second, it is portable and can be administered in clinics or using combinations of clinic based and home based administrations (Bechor et al, 2014; Eldar et al, 2012; Pergamin-Hight, Pine, Fox, & Bar-Haim, 2016; Rozenman, Weersing, & Amir, 2011). Third, it allows for efficient use of provider time and resources because the computer-based program does not require skilled clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it shows promising anxiety reduction effects in youth with anxiety disorders. In open trials (Bechor et al, 2014; Cowart & Ollendick, 2011; Rozenman et al, 2011) and randomized controlled trials (Eldar et al, 2012; Pergamin-Hight et al, 2016) using samples of youth with anxiety disorders, ABM has resulted in statistically significant reductions in anxiety symptoms (for reviews, see Lowther & Newman, 2014; Price et al, 2016). …”
Section: Introductionmentioning
confidence: 99%